Source - assembly - sink: Value added flows in the global economy - Robert Stehrer (The Vienna Institute for International Economic Studies (wiiw), 2021)
In this paper we provide a method to characterise global value chains and a related decomposition of bilateral gross exports by distinguishing three different stages of the value-added flows: (i) the source of value added, (ii) the final assembly stage of a product, and (iii) the final absorption (sink) of this product. Methodologically this is embedded in a simple framework using matrix algebra allowing for intuitive interpretations of the individual decomposition terms and results. The approach leads to a novel decomposition of bilateral gross export flows and related value-added trade indicators. It is shown how these correspond to existing measures using the property of inverse matrices. Specifically, the paper sheds light on the nature of the double-counting terms discussed in the literature. Finally, the approach outlined is extended by incorporating insights from the hypothetical extraction method. We argue that this is a complementary approach which however can be used to flexibly define the value chains of interest and characterise the respective flows that are considered part of this defined value chain, again carefully differentiating the source, assembly, and sink dimensions.
Keywords: F11; F14; F15; 330; global value chains; decomposition; gross exports; double-counting; hypothetical extraction